Adapting to change: Lived experiences of nursing students in rebuilding clinical confidence with limited face-to-face exposure - Abalona, Maricel D.; ajera, Sheilla M. Tr; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
The COVID-19 pandemic significantly reshaped nursing education, with the transition to remote learning impacting clinical confidence and competency development among student nurses. As nursing programs shift back to in-person learning, students face challenges in adapting to limited face-to-face clinical exposure, which serves as a critical bridge between theoretical knowledge and hands-on practice. This qualitative study employs descriptive phenomenology to explore the lived experiences of six nursing students—three third-level and three fourth-level—selected based on specific inclusion criteria. Data were gathered through one-on-one semi-structured Zoom interviews, and thematic analysis identified four key themes: (1) ineffective practical learning through virtual platforms, (2) limited face-to-face clinical exposure as a foundation for skill recovery, (3) challenges in transitioning from virtual to actual related learning experiences, and (4) fostering clinical confidence through personal preparation and adaptation. The findings highlight the difficulties students face in regaining hands-on competencies, adjusting to new learning modalities, and managing self-directed learning strategies to compensate for lost clinical immersion. Despite these challenges, limited face-to-face exposure was perceived as a step toward rebuilding clinical confidence, emphasizing the need for adaptable nursing curricula, enhanced simulation strategies, and structured transition programs. The study provides insights for educators, administrators, and policymakers in optimizing clinical education, ensuring students are adequately prepared for the evolving demands of professional nursing practice.